Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1073/pnas.93.3.1325
|View full text |Cite
|
Sign up to set email alerts
|

Increased dopamine turnover in the prefrontal cortex impairs spatial working memory performance in rats and monkeys.

Abstract: Increased dopamine turnover in the prefrontal cortex impairs spatial working memory performance in rats and monkeys (FG7142/RO15-1788 ABSTRACTThe selective activation of the prefrontal cortical dopamine system by mild stress can be mimicked by anxiogenic g3-carbolines such as FG7142. To investigate the functional relevance of elevated levels of dopamine turnover in the prefrontal cortex, the current study examined the effects of FG7142 on the performance of spatial working memory tasks in the rat and monkey. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
383
3
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 555 publications
(418 citation statements)
references
References 37 publications
31
383
3
1
Order By: Relevance
“…As noted above, acute administration of noncompetitive NMDA receptor antagonists is associated with a dramatic activation of dopamine transmission in forebrain (Doherty et al 1980;Bowers and Hoffman 1984;Deutch et al 1987;Verma and Moghaddam 1996;Jentsch et al 1997a), and this effect is likely directly implicated in the cognitive dysfunction exhibited by subjects acutely treated with PCP or ketamine (Verma and Moghaddam 1996), because increased dopamine transmission in prefrontal cortex has been reported to impair spatial working memory (Murphy et al 1996a;Jentsch et al 1997d). In rodents, an acute dose of PCP seems to augment prefrontal cortical and ventral striatal dopamine transmission; whereas, the dopaminergic innervation of the dorsal striatum is relatively unaffected (Deutch et al 1987;Jentsch et al 1997a).…”
Section: Neurochemistry Cortical Dopamine Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted above, acute administration of noncompetitive NMDA receptor antagonists is associated with a dramatic activation of dopamine transmission in forebrain (Doherty et al 1980;Bowers and Hoffman 1984;Deutch et al 1987;Verma and Moghaddam 1996;Jentsch et al 1997a), and this effect is likely directly implicated in the cognitive dysfunction exhibited by subjects acutely treated with PCP or ketamine (Verma and Moghaddam 1996), because increased dopamine transmission in prefrontal cortex has been reported to impair spatial working memory (Murphy et al 1996a;Jentsch et al 1997d). In rodents, an acute dose of PCP seems to augment prefrontal cortical and ventral striatal dopamine transmission; whereas, the dopaminergic innervation of the dorsal striatum is relatively unaffected (Deutch et al 1987;Jentsch et al 1997a).…”
Section: Neurochemistry Cortical Dopamine Dysfunctionmentioning
confidence: 99%
“…Likewise, novel antipsychotic agents, such as olanzapine and Seroquel, were observed to present PCP-induced prepulse inhibition deficits (Bakshi and Geyer 1995;Swerdlow et al 1996). Both clozapine and haloperidol have been reported to prevent stress-induced cognitive dysfunction in monkeys (Murphy et al 1996a), an effect mediated by heightened prefrontal cortical dopamine transmission (Murphy et al 1996b). Finally, we have reported that clozapine partially alleviated cognitive deficits in monkeys repeatedly treated with PCP (Jentsch et al 1997c).…”
Section: Response Of Pcp Effects To Antipsychotic Drugsmentioning
confidence: 99%
“…In animals with dopamine depletion, occurring either naturally with aging, or induced by reserpine treatment or chronic stress, the D 1 partial agonist SFK-38393 improves working memory (Arnsten et al, 1994;Mizoguchi et al, 2000). However, an overflow of dopamine activity, either by excessive dopamine release or overstimulation of postsynaptic D 1 receptor, can impair working memory (Arnsten and Goldman-Rakic, 1998;Cai and Arnsten, 1997;Murphy et al, 1996;Zahrt et al, 1997). These findings suggest that optimal functioning of PFC requires an intermediate level of dopamine input.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic exposure to the D 2 -like receptor antagonist haloperidol results in disrupted working memory (Castner et al, 2000). Acute challenge with various D 2 -like receptor antagonists has been reported to impair working memory and delayspecific PFC neuronal activity in some studies (Arnsten and Goldman-Rakic, 1998;Didriksen, 1995;Murphy et al, 1996), but not others (Aultman and Moghaddam, 2001;Bushnell and Levin, 1993;Sawaguchi and Goldman-Rakic, 1994;Verma and Moghaddam, 1996;Williams and GoldmanRakic, 1995). Working memory deficits induced by the noncompetitive NMDA antagonist ketamine (Verma and Moghaddam, 1996), the benzodiazepine inverse agonist FG-7142, or physiological stress (Arnsten and Goldman-Rakic, 1998) (Van Tol et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…However, the mesocortical dopaminergic neuromodulation is not straightforward, because the relation between prefrontal dopamine and 'cognitive performance' in memory tests depends on the nature of the task (Roberts et al, 1998). Thus, while prefrontal dopamine loss is known to impair performance on delayed alternation or delayed response in rats and monkeys (Murphy et al, 1996), the extinction of cued conditioned fear responses is delayed (Morrow et al, 1999), which indicates that the prefrontal cortex and its dopaminergic network 'organize' differently the behavioral response to varying motivational or mnesic demands (Roberts et al, 1998). In this respect, the effects of prefrontal dopamine loss in contextual fear conditioning or social interaction memory have not been explored.…”
Section: Introductionmentioning
confidence: 99%